THE EFFECTS OF BAP AND 2,4 D ON INITIATION AND INDUCTION OF PULESARI (Alyxia reinwardtii Blume) CALLUS - Nur Rahmawati Wijaya; Didik Suharto; Heru Sudrajat (Fakultas Pertanian, Universitas Janabadra, 2017)
Utilization of Pulesari as medicinal plant is less optimal due to scarcity and less known techniques of cultivation. To increase production of plant propagation it can use plant tissue culture especially callus formation. Research purpose: study effect of BAP and 2,4 D and knowing most appropriate hormone concentration for induction of Pulesari callus. Research using MS basal media with combination BAP 1-4 ppm and 2,4 D 1-4 ppm. Explant used pulesari leaf. Results: for three months showed treatment BAP + 2,4 D 4 ppm 1 ppm give fastest callus grow in 23 days after planting and highest amount of callus with surface area 3,4 cm2. Treatment of BAP 3 ppm + 2,4 D 1 ppm, as well as 4 ppm BAP + 2,4 D 4 ppm produce green callus, treatment of BAP 1 ppm + 2,4 D 1 ppm showed a yellowish white color, treatment BAP 1 ppm + 2,4 D 2 ppm, 2 ppm BAP + 2,4 D 4 ppm, and BAP 3 ppm + 2,4 D 4 ppm produce white callus. Callus with crumb texture produced by treatment of BAP 1 ppm + 2,4 D 3 ppm, BAP 1 ppm + 2,4 D 4 ppm, BAP 3 ppm + 2,4 D 2 ppm and BAP 3 ppm + 2,4 D 3 ppm while compact callus treatment resulted by BAP 2 ppm + 2,4 D 2 ppm, BAP 2 ppm + 2,4 D 3 ppm, BAP 4 ppm + 2,4 D 2 ppm and BAP 4 ppm + 2,4 D 3 ppm. Conclusion: BAP 4 ppm and 2,4 D 1 ppm accelerate callus grow. Best treatment is BAP 4 ppm+2,4D 1 ppm with hinghest amount of callus and fastest grow.